A unique case of Central Neurocytoma and concomitant brain AVM in a 12-year-old girl with long term follow up and review of the literature - Abbas Amirjamshidi; Kazem Abbasioun; Seyed Babak Ghasemi (Interdisciplinary Neurosurgery, 2024)
Background: Central Neurocytoma (CNCy) is an exceedingly rare brain tumor occurring within the ventricles in young adults. Anecdotal cases of CNCy occurring simultaneously with other brain lesions have been reported but to the best of our knowledge, no one was accompanied by brain AVM.Case presentation: A 12-year-old girl presented with signs of increased intracranial pressure. A multi-bleb CNCy originated from the septum in the midline, expanding to the lateral and third ventricles, back to the incisura and infratentorial- supra-cerebellar cistern concomitant with a left frontal parafalx AVM. The tumor excised successfully, and hydrocephalus controlled by ventriculoperitoneal shunting. The AVM bled after 7 years and was removed surgically. She is tumor free after 10 years. Conclusion: We present the first case of CNCy concomitant with brain AVM in a 12-year-old girl with more than 10 years follow up.